(untitled) (European Journal of Marketing and Economics, 2022)
The purpose of this study is to describe the possibility to initiate Finansial Technology (Fintech) as an innovation of communication technology on the credit cooperatives in Indonesia. This study is based on the phenomenon of tremendous growth of credit / financial business by using FinTech in Indonesia . Fintech so far has grew uncontrolablely among illegal financial institutions and gave unexpected impact on lower income people in Indonesia. On the other hand, the credit cooperatives as legal financial institutions which could facilitate lower income people for financial services lag behind. This study used quantitative-desciptive method, and resulted in some findings: (1) Cooperatives can become the fintech P2PL Platform model, as an alternative business model by changing conventional savings and loan businesses into the P2PL platform. The model could also be seen as a solution to prevent moral hazard due to miss-used of this technology among illegal credit instituions, (2) Fintech as an innovation is recognized feasible to apply. It has good relative advantage due to giving more efficiency and effectiveness on mana gement, it has good trialability because it may be easily experimented with on a limited basis, and has good observability because the result is visible to others, it has less complexity since it is easy to learn and apply. This study has implications for policies that fintech flatform model could be developed for credit cooperatives in Indonesia both in rural and urban areas..